Halogenated trimethoprim derivatives as multidrug-resistant Staphylococcus aureus therapeutics - Napon Nilchan (2019)
© 2018 Elsevier Ltd Incorporation of halogen atoms to drug molecule has been shown to improve its properties such as enhanced in membrane permeability and increased hydrophobic interactions to its target. To investigate the effect of halogen substitutions on the antibacterial activity of trimethoprim (TMP), we synthesized a series of halogen substituted TMP and tested for their antibacterial activities against global predominant methicillin resistant Staphylococcus aureus (MRSA) strains. Structure-activity relationship analysis suggested a trend in potency that correlated with the ability of the halogen atom to facilitate in hydrophobic interaction to saDHFR. The most potent derivative, iodinated trimethoprim (TMP-I), inhibited pathogenic bacterial growth with MIC as low as 1.25 μg/mL while the clinically used TMP derivative, diaveridine, showed resistance. Similar to TMP, synergistic studies indicated that TMP-I functioned synergistically with sulfamethoxazole. The simplicity in the synthesis from an inexpensive starting material, vanillin, highlighted the potential of TMP-I as antibacterial agent for MRSA infections.